Prevalence of simian malaria among macaques in Malaysia (2000-2021): A systematic review - Janeeca Sam; Nadia Aqilla Shamsusah; Amatul Hamizah Ali; Rozita Hod; Mohd Rohaizat Hassan; Hani Kartini Agustar (Public Library of Science (PLoS), 2022)
Background The aim of Malaysia to eliminate malaria nationwide by 2020 seems need to be prolonged. Whilst Malaysia has successfully eliminated human malaria transmission, simian malaria parasites such as Plasmodium knowlesi, P. cynomolgi, P. inui and P. cynomolgi are the emerging cause of malaria in humans. The epidemiological study of simian malaria in primates provides useful information in identifying the risk of human-macaques Plasmodium infection. Methodology/Principal findings This study was performed to gather all available data in terms of simian malaria epidemiology study among macaques in Malaysia over the last two decades. This systematic review was conducted according to the PRISMA guidelines to select appropriate articles as references. Data searches were performed through international databases such as Google Scholar, PubMed, CrossRef, Scopus, Web of Science and Science Direct for original articles published from 2000 until 2021. The review identified seven simian malaria epidemiology studies in Malaysia over the 20-year study period. Most studies were conducted in Peninsular Malaysia (5/7; 71%) followed by East Malaysia (2/7; 29%). All studies showed positive detection of Plasmodium parasites in macaques. The most prevalent Plasmodium species in macaques was P. inui (49.27%) and the least prevalent was P. fieldi (4.76%). The prevalence of simian malaria was higher in East Malaysia compared to Peninsular Malaysia. The mono, dual and triple infection types were the most common among macaques. Conclusion/Significance The non-human primates like macaques are the reservoir of simian plasmodium in Malaysia. Hence, the study of host epidemiology is an important insight to public health management as there is a high occurrence of simian malaria in Malaysia. The right measurement can be taken as well to prevent the transmission of simian malaria from macaques to humans. Author summary Macaques are the most abundant primates in south east Asia including Malaysia. Due to deforestation, macaques came closer to human settlements searching for food. Macaques like the long-tailed and pig-tailed harbouring several Plasmodium species that can cause zoonotic malaria in humans. Close contact of human and macaques cause zoonotic transmission of simian malaria. The simian plasmodium such as P. knowlesi, P. inui and P. cynomolgi have been found infecting humans in Malaysia; mainly in East Malaysia (Borneo). Zoonotic malaria poses great risk to public health as prolonged in treatment often lead to fatal outcomes. Hence the knowledge of prevalence and diversity is important to access, this can therefore enlighten the authorities to plan a control strategy that will minimize the zoonotic transmission between non-human primate host to human. This systematic review has summarised all publish data of macaques-plasmodium infection from the year 2000-2021 by using PRISMA guidelines. Our result showed that P. inui (49.27%) is the most prevalent Plasmodium species found in macaques, followed by P. cynomolgi (33.05%) and P. knowlesi (26.86%). Simian plasmodium prevalent was also found higher in East Malaysia (97.0%) compared to Peninsular Malaysia (45.18%). The significant increase of simian malaria incidences in human have jeopardized the national malaria elimination programme. Hence, this study provides a compact insight into the plasmodium epidemiology of macaques in Malaysia.